Unit cost expectations and uncertainty: Firms' perspectives on inflation - Brent H. Meyer; Nicholas B. Parker; Xuguang Sheng (Federal Reserve Bank of Atlanta, 2021)
We rely on the Atlanta Fed's Business Inflation Expectations survey to draw inference about firms' inflation perceptions, expectations, and uncertainty through the lens of firms' unit (marginal) costs. Using methods grounded in the survey literature, we find evidence that the concept of "aggregate inflation" as measured through price statistics like the consumer price index hold very little relevance for business decision makers. This lack of relevance manifests itself through experiments (including randomized controlled trials) that show how researchers word questions to elicit inflation expectations and perceptions significantly changes firms' responses. Our results suggest firms have become rationally ignorant of the concept of inflation in a low-inflation environment. Instead, we find that unit (marginal) costs are the relevant lens with which to capture firms' views on the nominal side of the economy. We then investigate both firm-level (micro) and aggregated (macro) probabilistic unit cost expectations. On a firm level, unit costs are an important determinant of firms' price-setting behavior. Aggregating across firms' beliefs, firms' unit cost perceptions strongly comove with official aggregate price statistics, and, importantly, firms' expectations for the nominal side of the economy have little in common with the "prices in general" expectations of households. Rather, firms' aggregated beliefs strongly covary with the inflation expectations of professional forecasters and market participants.
Keywords: E31; E52; 330; bimodality; inflation expectations; probability distributions; randomized controlled trials; uncertainty; unit cost